Model of resilience strategies of small and medium-sized tourism enterprises post pandemic crises in marine-based destination - Buntu Marannu Eppang; Herry Rachmat Widjaja; Muhammad Arifin; Muaz Azinuddin; Muhammad Arfin Muhammad Salim; Islahuddin (Journal of Applied Sciences in Travel and Hospitality, 2024)
This study investigates the resilience strategies employed by small and medium-sized tourism enterprises (SMTEs) in Tanjung Bira, a marine-based destination in South Sulawesi, Indonesia, to cope with the impact of the COVID-19 pandemic. Duchek's Model of resilience, which conceptualizes resilience as a meta-capability composed of three stages (anticipation, coping, and adaptation), is used as a key framework. An exploratory qualitative approach was employed, involving in-depth semi-structured interviews with seven informants representing various tourism stakeholders. Thematic analysis revealed several main strategies for SMTE resilience: collaboration with stakeholders, government intervention, implementation of digital marketing, strengthening SMTEs legality, and strengthening/diversification of SMTE products. Mapping these strategies onto Duchek's Model, the anticipation stage included strategic planning, risk assessment, and building dynamic capabilities; the coping stage consisted of immediate financial measures and policy support; and the adaptation stage involved diversification, technology and innovation adoption, and collaboration and networking. A key implication is that destination management organizations should create innovative products and leverage online platforms for marketing to increase visitor arrivals and boost SMTE product sales. The findings contribute to understanding SMTE resilience in the context of a marine-based destination in Eastern Indonesia and provide insights for policymakers and practitioners to support SMTE recovery and long-term sustainability post-pandemic.